The concept of Circular Supply Chain Management (CSCM) / Mohd Rizaimy Shaharudin ... [et al.] - Shaharudin, Mohd Rizaimy; Hassam, Siti Fairuza; Zainal, Nur Diyana Nazihah; Mohamad Mokhtar, Ahmad Rais; Wararatchai, Preecha; Aunyawong, Wissawa; Nuanklao, Suwat (2019)
Seventeen Sustainable Development Goals (SDGs) of the 2030 Agenda for Sustainable Development has been signed by the by world leaders in September 2015 and officially commenced on 1st January 2016. It is expected that in the next fifteen years, each of the countries will intensify their efforts to combat poverty, the battle for discriminations and tackle the environmental issues. Concerning this, Goal 12 of SDGs clearly described the objective towards sustainable consumption and manufacturing operations, to promote the efficiency in resource and energy usage, infrastructure viability, accessibility to the vital services, environmental and productive employment and well-being for the people. The adoption of SDGs enables a country to achieve development targets, mitigate economic, ecological and social costs, enhance the financial performance and lower the poverty. As such, there is a need to focus on supply chain effectiveness in manufacturing, from producer to the final consumer. This requirement resonates the critical application of circular supply chain management (CSCM) in manufacturing operations. Unlike the closed-loop supply chain (CLSC) in the circular economy, firms collaborate with another firm in the same as well as different industry to maximize the salvage value and zero waste. Nevertheless, it was discovered that CSCM topic had been insufficiently discussed in the literature, as in principle, the field is still new under the domain of circular economy. In Malaysia, there is no proactive effort to recover or recycle end-of-life products and the returns in CSCM. On a similar extent, in Thailand, the management of natural resources and the environment has been ineffective, exacerbated the natural resources depletion and degradation of environmental quality. This circumstance will put the countries in difficulties to achieve the SDG goals.